Effect of high dilutions of Arsenicum album on wheat seedlings from seed poisoned with the same substance - Betti, L.; Brizzi, M.; Nani, D.; Peruzzi, M. (British Homeopathic Journal, 1997)
A blind laboratory experiment was carried out to show the effect of a 45x potency of Arsenicum album (As2O3) on wheat seedlings whose seeds had been previously poisoned with a material dose of the same substance. The effect of the homoeopathic treatment on stem growth was statistically significant. The experimental results were matched with a previous study concerning homoeopathic treatment in the same species.